The Need for Implementing Control on Political Parties Funding: Editorial - Zuberi, Kaukab Jamal (International Journal for Electronic Crime Investigation, 2021)
Internet has become a part of our life. Weuse internet to search information, delivereducation, communicate with each other,doing medical operations, entertainment andmonitor various devices ranging from CCTVcameras to pacemakers. Cyber worldtherefore, is a space on which we aredepending by one way or other every singleday. Among the broadband networks,beneath us, and the wireless signals aroundus, the local networks in our schools,hospitals and businesses, and the massivegrids that power our nation, classifiedmilitary and intelligence networks that keepus safe, and the World Wide Web that hasmade us more interconnected than any timein human history. It is a great irony of ourcyber age that the technology which enablesus to create, build and facilitate our lives alsoempowers those who would disturb anddestroy.